Sebaran kandungan CO2 terlarut di perairan pesisir selatan Kepulauan Natuna - August Daulat; Mariska Astrid Kusumaningtyas; Rizki Anggoro Adi; Widodo Setiyo Pranowo (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
Abstract. Biogeochemical cycles in coastal ecosystem is influencing the water quality and it is further affect on productivity and sustainability of coastal waters. Carbondioxide is one of the important parameter in biogeochemical cycles in coastal waters, it is formed as DIC (Dissolved Inorganic Carbon) in water and TOC (Total Organic Carbon) in sediment. The purpose of this research was to determine the distribution concentration of dissolved CO2 in the southern coastal waters of Natuna Islands. Insitu measurement was conducted for some parameters of water qualities both physical (i.e. temperature and turbidity) and chemical (i.e. DO, pH and salinity) parameters. DIC was analyzed in LIPI laboratory using Giggenbach titration method, while TOC in sediment was analyzed in Proling Laboratory, Institut Pertanian Bogor. The water quality of the southern coastal waters of Natuna Islands generally in a good condition according to the Ministry of Environment Decree, Number 51, year 2004. The results showed that spacial distribution of DIC ranged from 1.9 to 2.3 mol/kg, while TOC content of the water was ranged from 0.25 g/kg to 1.19 g/kg. Sediment distributions were dominated by sandy, silty sand, sandy silt and coral reefs, therefore the sediment has potencial as organic carbon storage and indicates a good productivity.Keywords: Carbondioxide; Dissolved Inorganic Carbon; Total Organic Carbon; Natuna Islands Abstrak. Siklus biogeokimia yang terjadi pada ekosistem pesisir dapat mempengaruhi kualitas perairan dan berfungsi sebagai penunjang keberlanjutan dan kesuburan perairan. Karbondioksida adalah salah satu parameter penting dalam siklus biogeokimia di perairan pesisir baik berupa DIC (Dissolved Inorganic Carbon) di dalam air maupun berupa TOC (Total Organic Carbon) di dalam sedimen. Penelitian ini bertujuan untuk mengetahui sebaran kandungan CO2 terlarut di perairan pesisir selatan Kepulauan Natuna. Pengukuran insitu dilakukan terhadap beberapa parameter kualitas air baik fisika (temperatur dan kecerahan) maupun kimia (DO, pH dan salinitas). Metode titrasi Giggenbach digunakan untuk analisis DIC di laboratorium LIPI, sedangkan TOC dalam sedimen dianalisis di laboratorium Proling, IPB. Kualitias air di perairan pesisir selatan Kepulauan Natuna secara umum masih berada dalam kondisi baik berdasarkan Keputusan Menteri Negara Lingkungan Hidup No. 51 tahun 2004. Hasil penelitian menunjukan sebaran spasial parameter kandungan CO2 dengan kandungan DIC berkisar antara 1,9-2,3 mol/kg, sedangkan kandungan TOC perairan berkisar antara 0,25-1,19 g/kg. Sebaran sedimen didominasi oleh pasir, pasir lanau, lanau pasiran dan terumbu karang yang berpotensi besar menyimpan karbon organik didalam sedimennya dan mengindikasikan kesuburan perairan pesisir selatan Kepulauan Natuna tergolong baik.